The impact of prebiotic, probiotic, and synbiotic supplements on CD4, CD8 counts and inflammatory markers in HIV patients: A systematic review and meta-analysis - Sirait, Josephine Claudia; Prabandari, A.A. Sagung Mirah; Wijanadi, M. Candra; Harimawan, Agustinus Wayan; Sutadarma , I Wayan Gede (Indonesian Nutrition Association, 2024)
HIV infection compromises immune function and depletes CD4+ T-lymphocytes. Prebiotics, probiotics, and synbiotics are potential dietary supplements to improve immune status and manage inflammation in HIV patients. This systematic review and meta-analysis investigated their effects on CD4 count, CD8 count, and inflammatory markers in HIV patients.